Evaluating complex transformation: British Columbia's provincial response to the overdose public health emergency. Issue 3 (6th November 2019) - Best, Allan; Ong, Narelle; Cooper, Penny; Davison, Carolyn; Coatta, Katherine; Berland, Alex; Herbert, Carol; Mitton, Craig; Millar, John; Reichert, Stephen; Cano, Allison
Abstract : Purpose: The purpose of this paper is to present a detailed case study of the evaluation strategies of a complex, multi-faceted response to a public health emergency: drug-related overdose deaths. It sets out the challenges of evaluating such a complex response and how they were overcome. It provides a pragmatic example of the rationale and issues faced to address the what, the why and particularly the how of the evaluation. Design/methodology/approach: The case study overviews British Columbia's Provincial Response to the Overdose Public Health Emergency, and the aims and scope of its evaluation. It then outlines the conceptual approach taken to the evaluation, setting out key methodological challenges in evaluating large-scale, multi-level, multisectoral change. Findings: The evaluation is developmental and summative, utilization focused and system informed. Defining the scope of the evaluation required a strong level of engagement with government leads, grantees and other evaluation stakeholders. Mixed method evaluation will be used to capture the complex pattern of relationships that have informed the overdose response. Working alongside people with drug use experience to both plan and inform the evaluation is critical to its success. Originality/value: This case study builds on a growing literature on evaluating large-scale and complex service transformation, providing a practical example of this.